PRARANCANGAN PABRIK FURFURAL DARI TONGKOL JAGUNG KAPASITAS 13.000 TON/TAHUN - , ANRO YEDI MUNTHE ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Furfural plant from corncobs with capacity 13.000 tons per year need corncobs 16706.76 kg / hour, water 31061 kg / hour and H2SO4 98% 13543 kg / hour as the raw material. This plant will obtain furfural with 98.5% purity. The process will be occur as follow: pentosan in corn cobs is hydrolyzed into pentose, then pentose become furfural by dehydration reaction. This reaction need H2SO4 as catalyst. Furfural formed in solids corn cobs will be taken by steam with 10 atm and temperature 667oC which flowed countercurrent to the reactor. Furfural will be carried away by the steam condensed in the condenser. Furfural solution will be purified in the extractor and distillation column to produce furfural with the desired purity. This plant will be established in Tuban, East Java, which occupies a land area about 8 ha, with a 182 person workforce. The plant will operate continuously for 24 hours / day for 330 days / year. Based on the economic evaluation, this plant need fixed capital of US$ 11,363,134.17 + Rp 134.238.559.995,68 and working capital of US$. 393,732.60 + Rp. 50.568.800.110,82. Break Even Point (BEP) of 50,47% (BEP restrictions in Indonesia 40% - 60%) and Shut Down Point of 21,11% and Return On Investment (ROI) before taxes 40,47% (ROI limits for plants with low risk> 11%). Pay Out Time (POT) before tax for the year of 3.31 (low risk plant POT limit <5 years). Discounted Cash Flow Rate of Return (DCFRR) of 27,52% with an average interest rate in the bank 15% - 20%. From the analysis it can be concluded that this plant is quite interesting to study further. Keywords: furfural, corncobs, hydrolize, dehidration